Mild solutions for nonlocal fractional semilinear functional differential inclusions involving Caputo derivative - Ahmed G. Ibrahim; Noriah Almoulhim (Le Matematiche, 2014)
In this paper, we prove various existence results of a mild solution for a fractional nonlocal functional semilinear differential inclusion involving Caputo derivative in Banach spaces. We consider the case when the values of the orient field are convex as well as nonconvex. Moreover, we study the topological structure of solution sets. Our results extend or generalize results proved in recent papers.